PENGARUH PENERAPAN STRATEGI PEMBELAJARAN PQ4R TERHADAP HASIL BELAJAR SISWA KELAS IX MTsN 1 PESISIR SELATAN - delyana, hafizah - (Jurnal Pelangi : Research of Education and Development, 2017)
This Research was based on student’s mathematics learning outcome was still under Minimum Achievement Criteria (KKM). The research was aimed at finding out whether student’s mathematical learning outcome by implementing PQ4R strategy was better than student’s mathematics learning outcome by implementing conventional learning at class IX MTsN 1 Pesisir Selatan. This was an experimental research with research result is random to subject. The population was all students at IXMTsN 1 Pesisir Selatan. Sampling classes were class IX.6 as the experimental class and IX.5 as the control class. The instrument was final test with its reliability 0,98. Technique of data analysis used one-tailed t-test. Based on the result of data analysis, it is concluded that student’s mathematical learning outcome by implementing PQ4R strategy was better than student’s mathematics learning outcome by implementing  convensional learning.